Waves and fields in inhomogeneous media - Chew, Weng Cho (IEEE Press, 1995)
Electrical Engineering/Electromagnetics Waves and Fields in Inhomogeneous Media A Volume in the IEEE Press Series on Electromagnetic Waves Donald G. Dudley, Series Editor ".it is one of the best wave propagation treatments to appear in many years." Gerardo G. Tango, CPG, Consulting Seismologist-Acoustician, Covington, LA This comprehensive text thoroughly covers fundamental wave propagation behaviors and computational techniques for waves in inhomogeneous media. The author describes powerful and sophisticated analytic and numerical methods to solve electromagnetic problems for complex media and geometry as well. Problems are presented as realistic models of actual situations which arise in the areas of optics, radio wave propagation, geophysical prospecting, nondestructive testing, biological sensing, and remote sensing.
Originally published: New York : Van Nostrand Reinhold, c1990
Description based on PDF viewed 12/21/2015
Keywords: Electromagnetic fields; Electromagnetic waves; Welle; Inhomogenes Medium; Elektromagnetisches Feld; Wellenausbreitung